Type effect of inhibitory KT tape on measured vs. perceived maximal grip strength. Issue 3 (July 2018) - MacPhail, Aislinn Joan Campbell; Au, Ivan Pui-Hung; Chan, Mavis; Mak, Dominic Ngo-Tung; An, Winko Wenkang; Chan, Zoe Yau-Shan; Zhang, Janet Hanwen; Wong, Kenny; So, Ann; Chan, Nora; Kwok, Chris; Lau, Patrick; et al.
Abstract: This study examined the effects of KT tape (KT) applied in an inhibitory manner on muscle activity, measured maximal grip strength, and perceived maximal grip strength in regular KT-users and non-users. This study was a single-blinded crossover study with sixty participants including 27 kT-users and 33 non-users. Participants underwent maximal grip strength tests with and without inhibitory KT applied across the wrist extensors. Muscle activity and maximal grip strength were measured, while perceived maximal grip strength was rated using a visual analogue scale. No significant interaction effect was found between taping conditions and participant KT-experience for muscle activity ( F = 0.825, p = 0.367), measured grip strength ( F = 1.018, p = 0.317) or perceived grip strength ( F = 0.122, p = 0.728). No significant differences were observed in the EMG activity between taping conditions for either KT-users (p = 0.367) or non-users ( p = 0.215). A similar trend was found in the measured grip strength (KT-users: p = 0.317; non-users: p = 0.294) and perceived grip strength (KT-users: p = 0.728; non-users: p = 0.063). KT applied in an inhibitory manner does not impede EMG activity, measured maximal grip strength, or perceived maximal grip strength in adults, regardless of their preconceived notions of KT.